The association of diet carbohydrates consumption with cognitive function among US older adults modification by daily fasting duration - Zhao, Shengnan; Han, Tianshu; Pei, Xinyi; Song, Yuhua; Zhang, Yuntao; Liu, Lin; Wang, Xuanyang; Hou, Wanying; Sun, Changhao (Frontiers in Aging Neuroscience, 2022)
Background: Few studies investigate the association of dietary carbohydrate consumption with cognitive function modification by daily fasting duration. Methods: In this cross-sectional study, 2485 adults aged over 60 years from the nationally representative data of the National Health and Nutrition Examination Survey (NHANES, 2011-2014) were enrolled. Percentage energy from carbohydrates was present in both quartiles and continuous forms. Daily fasting duration = 24 - (timing for dinner - breakfast). Cognitive function was assessed by the Consortium to Establish a Registry for Alzheimer’s Disease Word List Learning (CERAD-WL), CERAD Word List Delayed Recall (CERAD-DR), Animal Fluency (AF), and Digit Symbol Substitution (DSST) Test. Multiple logistic regression and linear regression models were developed to examine the association of dietary carbohydrates with cognitive function among participants with different daily fasting duration. Restricted cubic spline models were also applied. Results: Compared with the lowest quartile of percentage energy from carbohydrates, the highest quartile had higher ORs of poor cognitive performance among total participants [(ORCERAD-WL 1.84 95% CI 1.25-2.71); (ORCERAD-DR 1.45 95% CI 1.10-1.91)] and participants with daily fasting duration fewer than 16 hours [(ORCERAD-WL 2.14 95% CI 1.29-3.55); (ORCERAD-DR 1.51 95% CI 1.05-2.17)] but not in participants with daily fasting duration of more than 16 hours. Further, the negative associations between percentage energy from carbohydrates and CERAD-WL score were still significant in addition to participants whose daily fasting duration was more than 16 hours. Additionally, dose-response associations were detected between dietary carbohydrates and cognitive decline, while “U” curves were observed among participants whose daily fasting duration was more than 16 hours. Conclusions: This study indicated that dietary carbohydrates consumption was associated with poor cognitive performance, but not in participants whose daily fasting duration was more than 16 hours among US older adults. The current analysis provides evidence that a longer daily fasting duration may improve the harmful effect of dietary carbohydrates on cognitive function.